Activation of vitamin D in the gingival epithelium and its role in gingival inflammation and alveolar bone loss. (25th February 2019) - Menzel, Lorenzo P.; Ruddick, Willam; Chowdhury, Mobaswar H.; Brice, David C.; Clance, Ryan; Porcelli, Emily; Ryan, Lisa K.; Lee, Jungnam; Yilmaz, Özlem; Kirkwood, Keith L.; McMahon, Laura; Tran, Amy; et al.
Abstract : Background and Objective: Both chronic and aggressive periodontal disease are associated with vitamin D deficiency. The active form of vitamin D, 1, 25(OH)2 D3, induces the expression of the antimicrobial peptide LL‐37 and innate immune mediators in cultured human gingival epithelial cells (GECs). The aim of this study was to further delineate the mechanism by which vitamin D enhances the innate defense against the development of periodontal disease (PD). Materials and Methods: Wild‐type C57Bl/6 mice were made deficient in vitamin D by dietary restriction. Cultured primary and immortalized GEC were stimulated with 1, 25(OH)2 D3, followed by infection with Porphyromonas gingivalis, and viable intracellular bacteria were quantified. Conversion of vitamin D3 to 25(OH)D3 and 1, 25(OH)2 D3 was quantified by ELISA. Effect of vitamin D on basal IL‐1α expression in mice was determined by topical administration to the gingiva of wild‐type mice, followed by qRT‐PCR. Results: Dietary restriction of vitamin D led to alveolar bone loss and increased inflammation in the gingiva in the mouse model. In primary human GEC and established human cell lines, treatment of GEC with 1, 25(OH)2 D3 inhibited the intracellular growth of P. gingivalis . Cultured GEC expressed two 25‐hydroxylases (CYP27A1 and CYP2R1), as well as 1‐α hydroxylase, enabling conversion of vitamin D to both 25(OH)D3 and 1, 25(OH)2 D3 . Topical application of both vitamin D3 and 1, 25(OH)2 D3 to the gingiva of mice led to rapid inhibition of IL‐1α expression, a prominent pro‐inflammatory cytokine associated with inflammation, which also exhibited more than a 2‐fold decrease from basal levels in OKF6/TERT1 cells upon 1, 25(OH)2 D3 treatment, as determined by RNA‐seq. Conclusion: Vitamin D deficiency in mice contributes to PD, recapitulating the association seen in humans, and provides a unique model to study the development of PD. Vitamin D increases the activity of GEC against the invasion of periodontal pathogens and inhibits the inflammatory response, both in vitro and in vivo. GEC can convert inactive vitamin D to the active form in situ, supporting the hypothesis that vitamin D can be applied directly to the gingiva to prevent or treat periodontal disease.